Enhancing Students’ Learning Motivation Through the Implementation of the Discovery Learning Model - Adeline Silaban; Jan Pieter; Putu Victoria M R; Siti Hajar; Desy C Silaban (Jurnal Penelitian Pendidikan IPA, 2026)
The implementation of this study aims to examine how students’ learning motivation develops during the discovery learning process supported by authentic assessment. Low motivation significantly contributes to poor engagement, reduced persistence, and lower learning outcomes. The research employs a descriptive qualitative design. Data analysis is conducted for all collected data, encompassing both quantitative and qualitative sources. Based on the N-Gain calculation, the experimental class had an average N-Gain of 0.53, which is considered moderate, while the control class had an average N-Gain of 0.29, which is considered low. This indicates that applying the Discovery Learning model in the experimental class led to a greater increase in learning motivation than that of conventional learning in the control class.